PAJAK REKLAME: UPAYA UNTUK MENINGKATKAN KONTRIBUSI PENDAPATAN ASLI DAERAH DI KABUPATEN BREBES - Zumaeroh Zumaeroh; Agus Prabawa (FEB UNWIKU PURWOKERTO, 2020)
Every regional government is required to be able to optimize the potential of its regional income, including from the regional tax sector. One of the taxes managed by the local government is the advertisement tax. Brebes Regency, as one of the areas in Central Java Province which are traversed by the main route of the Urata coast (Pantura), is expected to be able to optimize regional income from advertisement tax. However, the advertisement tax obtained in Brebes Regency is still not optimal. Based on this, this study seeks to determine the performance of the advertisement tax on local revenue in Brebes Regency. With secondary data, this research was conducted using a quantitative approach. Data obtained from the Regional Revenue Service of Brebes Regency. The method of calculating advertisement tax data is calculated based on the Regional Regulation of Brebes Regency number 8 of 2010. Then the data is carried out several analyzes to determine the growth, contribution, and effectiveness. Also, SWOT analysis is used to determine the position of strengths, weaknesses, opportunities, and threats from the implementation of billboard tax collection in Brebes district. The advertisement tax in Brebes Regency has enormous potential, especially in several Districts that are traversed by the northern coast (pantura) such as Brebes District, Losari District, and Bulakamba District. Based on the results of the analysis, the growth of advertisement tax revenue realization in Brebes Regency was 80.27%. Based on this, the contribution analysis shows that the advertisement tax in Brebes Regency is still very low. Based on the results of the SWOT analysis, the implementation of advertisement tax revenue in Brebes Regency has weaknesses, especially in the limitations of the system, and human resources. However, the advertisement tax in Brebes Regency has a great opportunity to be developed into a source of regional income